Adrenal crisis in a 14-year-old boy 12 years after hematopoietic stem cell transplantation - Penger, Theresa; Albrecht, Andrea; Marx, Martin; Stachel, Daniel; Metzler, Markus; Dörr, Helmuth-Günther (Endocrinology, Diabetes and Metabolism Case Reports, 2018)
We report on a boy of Albanian descent with the history of juvenile myelomonocytic leukemia (JMML). JMML was diagnosed at the age of 17 months and treated by hematopoietic stem cell transplantation (HSCT). At the age of 14.3 years, about 12 years after HSCT, he was hospitalized with an adrenal crisis. Hormone findings were consistent with primary adrenal insufficiency. Autoimmune adrenalitis was confirmed by positive autoantibodies against 21-hydroxylase and adrenal tissue. Since autoimmune Hashimoto thyroiditis was already known from the age of 9 years, we assume that both diseases are part of the spectrum of autoimmune polyglandular syndrome (APS) type 2. APS type 2 is a rare endocrine disease characterized by Addison's disease along with autoimmune thyroid disease and/or type 1 diabetes. Learning points: Endocrine sequelae after hematopoietic stem cell transplantation (HSCT) are common and can develop over a long period.Primary adrenal insufficiency after HSCT is absolutely rare.The combination of adrenal autoimmune disease and Hashimoto thyroiditis is consistent with autoimmune polyglandular syndrome type 2.
EVALuna2:35483

Adrenarche and pubarche in girls with turner syndrome during growth-promoting therapy with human growth hormone - Dörr, Helmuth-Günther; Penger, Theresa; Marx, Martin; Rauh, Manfred; Oppelt, Patricia; Völkl, Thomas (BMC Endocrine Disorders, 2019)
Background: Data on adrenarche and pubarche in girls with Turner syndrome (TS) are inconsistent in the literature. Methods: The cohort consisted of 94 girls and young women with TS born between 1971 and 2001 (age range: 3.1-23.2 yrs.), who were treated with human growth hormone and regularly presented at our outpatient clinic every 4 to 6 months.The longitudinal data of all patients were ascertained retrospectively from patient charts. The data collection ended in January 2016. Adrenarche was assessed by serum DHEAS levels and pubertal status by Tanner stages. Pubarche was defined as the appearance of pubic hair (PH2), whereas spontaneous puberty was defined as Tanner stage B2. The patients were retrospectively subdivided in two groups with regard to pubertal development: group 1 (n = 21) with spontaneous puberty and group 2 (n = 70) with induced puberty. Since blood samples were not taken at every visit, we generated seven groups according to the age of the children at which the blood samples were taken: 3-5, 5-7, 7-9, 9-11, 11-13, 13-15, and 15-17 yrs. Serum DHEAS and follicle-stimulating hormone (FSH) levels were measured by chemiluminescence immunoassay and compared with those of a control group of healthy girls. Results: Adrenarche started in TS girls between 5 and 7 years. TS girls had higher DHEAS levels than the control group, with statistically significant differences in the age groups 7 to 17 years. No differences were determined between the TS girls with spontaneous puberty and those with POI. TS girls in group 2 reached the Tanner stages PH2 (p < 0.04), PH3 (p < 0.01), PH4 and PH5 (p < 0.001) markedly later than TS girls in group 1. Conclusions: The onset of adrenarche in girls with TS undergoing GH therapy does not differ from that in healthy girls. However, adrenarche is more pronounced in girls with TS. There is no difference in DHEAS levels between the TS girls with spontaneous puberty and the TS girls with primary ovarian insufficiency (POI), while the tempo of pubarche is markedly slower in the girls with POI.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Adrenarche; DHEAS; Primary ovarian insufficiency; Turner syndrome

BDV Syndrome: An Emerging Syndrome with Profound Obesity and Neurodevelopmental Delay Resembling Prader-Willi Syndrome - Bosch, Elisabeth; Hebebrand, Moritz; Popp, Bernt; Penger, Theresa; Behring, Bettina; Cox, Helen; Towner, Shelley; Kraus, Cornelia; Wilson, William G.; Khan, Shagufta; Krumbiegel, Mandy; Ekici, Arif Bülent; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: CPE encodes carboxypeptidase E, an enzyme that converts proneuropeptides and propeptide hormones to bioactive forms. It is widely expressed in the endocrine and central nervous system. To date, 4 individuals from 2 families with core clinical features including morbid obesity, neurodevelopmental delay, and hypogonadotropic hypogonadism, harboring biallelic loss-of-function (LoF) CPE variants, have been reported. Objective: We describe 4 affected individuals from 3 unrelated consanguineous families, 2 siblings of Syrian, 1 of Egyptian, and 1 of Pakistani descent, all harboring novel homozygous CPE LoF variants. Methods: After excluding Prader-Willi syndrome (PWS), exome sequencing was performed in both Syrian siblings. The variants identified in the other 2 individuals were reported as research variants in a large-scale exome study and in the ClinVar database. Computational modeling of all possible missense alterations allowed assessing CPE tolerance to missense variants. Results: All affected individuals were severely obese with neurodevelopmental delay and other endocrine anomalies. Three individuals from 2 families shared the same CPE homozygous truncating variant c.361Câ€ >â€ T, p.(Arg121∗), while the fourth carried the c.994del, p.(Ser333Alafs∗22) variant. Comparison of clinical features with previously described cases and standardization according to the Human Phenotype Ontology terms indicated a recognizable clinical phenotype, which we termed Blakemore-Durmaz-Vasileiou (BDV) syndrome. Computational analysis indicated high conservation of CPE domains and intolerance to missense changes. Conclusion: Biallelic truncating CPE variants are associated with BDV syndrome, a clinically recognizable monogenic recessive syndrome with childhood-onset obesity, neurodevelopmental delay, hypogonadotropic hypogonadism, and hypothyroidism. BDV syndrome resembles PWS. Our findings suggest missense variants may also be clinically relevant.
CRIS-Team Scopus Importer:2021-12-24
Keywords: BDV syndrome; carboxypeptidase E; CPE; hypogonadotropic hypogonadism; neurodevelopmental disorder; obesity

Betreuung von Kindern und Jugendlichen mit M. Basedow in einem endokrinologischen Zentrum - Penger, Theresa; Albrecht, Andrea; Marx, Martin; Jüngert, Jörg M.; Kuwert, Torsten; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2019)
Background: Graves’ disease is rare in childhood and adolescence. While the criteria for diagnosis are clearly defined, there are controversial discussions in the literature regarding the optimal treatment modality. Objective: The aim of the study was to retrospectively analyze the treatment and long-term course of patients with Graves’ disease who were under the care of this outpatient department of pediatric endocrinology between 2000 and 2015. Material and methods: The data of 50 children and adolescents (40 female, 10 male) aged between 4.5 and 17.6 years (median 12.4 years) were evaluated. The patient history, height, weight and laboratory values were documented at the initial presentation and at every outpatient visit. The duration to achievement of euthyroidism (remission), the time until attempted withdrawal, the duration of remission, the time of recurrence and the time and type of a final treatment were also documented. To calculate thyroid volume (SDS) values, the data of Kromeyer-Hauschild et al. were used as references for height and BMI and for the sonographically measured thyroid volume the data of the German National Health Examination Survey for Children and Adolescents (KiGGS) were used. Results (median values): The diagnosis was made 6 months after the onset of symptoms at the age of 12.4 years. Serum thyroid-stimulating hormone (TSH) levels were suppressed, free tri-iodothyronine (fT3, 21.6 pmol/l; normal range 3.5–8.1), free thyroxine (fT4, 48.3 pmol/l; 7.6–17.7), and TSH-receptor antibody (TRAB, 9.4 U/l; <1.5) were elevated. At diagnosis 28 children had goiter (+5.9 SDS) and 15 patients developed a goiter during the further course. All patients primarily received thiamazole (n = 34) or carbimazole (n = 16) and 18 patients a beta blocker. During the course 96% received dual therapy (antithyroid drug plus L‑T4) and 9 patients are still receiving primary treatment. Thus, 41 patients could be assessed with respect to the long-term course. The treatment did not affect the size of the thyroid gland. A withdrawal trial was performed in 33 patients at 32 months, including 6 patients receiving treatment for <24 months and 11 patients receiving treatment for more than 36 months. Thyroidectomy was performed in 8 patients on drug treatment without a withdrawal trial due to the increasing goiter. After the end of the thyrostatic therapy, 17 patients achieved full remission (no recurrence of hyperthyroidism after completion of drug treatment) and 8 patients currently have a remission duration ≥12 months. Recurrence treatment was initiated in 7 patients after the first remission and 9 patients underwent thyroidectomy. Conclusion: The high remission rate was positively correlated with the treatment duration. The dual therapy regimen might also affect the outcome. The size of the thyroid gland was unchanged during treatment. The extent of TRAB levels at the time of the withdrawal trial did not affect the long-term outcome. In all cases with a rapid goiter progression, an early thyroidectomy should be performed.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Hyperthyroidism; Long-term outcome; Single center; Therapeutic options

Birth Size in Neonates with Congenital Adrenal Hyperplasia due to 21-hydroxylase Deficiency - Dörr, Helmuth-Günther; Penger, Theresa; Albrecht, Andrea; Marx, Martin; Völkl, Thomas (JCRPE Journal of Clinical Research in Pediatric Endocrinology, 2019)
Objective: Classic congenital adrenal hyperplasia (CAH) secondary to 21-hydroxylase deficiency is characterized by increased prenatal adrenal androgen secretion. There are a small number of reports in the literature showing higher birth weight and length in CAH newborns.
CRIS-Team WoS Importer:2019-03-06

Ektope Lage einer Schilddrüse im Zungengrund – Zufallsdiagnose bei einem 6‑jährigen Mädchen - Albrecht, Andrea; Penger, Theresa; Marx, Martin; Jüngert, Jörg M.; Kuwert, Torsten; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2020)
Background: An ectopic thyroid gland is a rare anomaly due to the incomplete descent of the thyroid gland during the embryonic developmental migration process. The ectopic thyroid tissue is normally located in the area from the tongue to the diaphragm but lingual and sublingual locations preferentially occur. In a child with congenital hypothyroidism, which was detected during neonatal screening, the ectopic gland could be diagnosed during the further clarification. Case report: This article reports on the case of a girl who was presented to the pediatrician for clarification of chronic abdominal pain at the age of 6 years and 3 months. As an incidental finding the pediatrician diagnosed a subclinical hypothyroidism (serum TSH 23.3 mU/l, fT3 and fT4 normal) and initiated treatment with L‑thyroxine (L-T4). The psychomotor, growth and weight development had always been age-appropriate. At the initial presentation in this outpatient department the girl was 6 years and 5 months old, was clinically and biochemically euthyroid, and the body measurements were normal. The thyroid autoantibodies were inconspicuous. The ultrasound scan revealed a small lingual thyroid-like tissue (volume 0.9 ml) with no thyroid tissue in the typical site. A thyroid scintigraphy confirmed the diagnosis. Under the weight-adapted medication with L‑thyroxine the patient never developed symptoms of hypothyroidism and the volume of the lingual thyroid did not increase. The patient is currently 11 years and 8 months old (height 146.9 cm, weight 33.3 kg, Tanner stage B 2) and attends a grammar school. Conclusion: A thyroid gland at the base of the tongue is a rare cause of latent hypothyroidism and is difficult to diagnose when there is a lack of clinical symptoms. It can be detected at any age as an incidental finding.
CRIS-Team Scopus Importer:2020-05-05
Keywords: Ectopic lingual thyroid; Incidental finding; Rare disease; Subclinical hypothyroidism; Thyroid ultrasound

Miscarriages in families with an offspring that have classic congenital adrenal hyperplasia and 21-hydroxylase deficiency - Dörr, Helmuth-Günther; Hess, Johannes; Penger, Theresa; Marx, Martin; Oppelt, Patricia (BMC Pregnancy and Childbirth, 2018)
BACKGROUND: The most common form of congenital adrenal hyperplasia is 21-hydroxylase deficiency (CAH). Both men and women with classic CAH have lower fertility rates than the general population, and an increased rate of miscarriages has been reported in affected women. There are no data on the incidence rate of miscarriages in families with an offspring that have classic CAH. METHODS: We studied families with a history of classic CAH. The families came from different parts of Germany and attended the annual meeting of the German CAH support group for parents and patients which was held in Hamburg in September 2014. The data was collected anonymously by a paper-based questionnaire which was completed by the families at home. The families also accepted the responsibility to address this question to their siblings. In all, the data of 50 families with at least one child with classic CAH, and the data of 164 parental siblings were available for evaluation. Miscarriage rates were calculated in relation to the reported pregnancies. RESULTS: Twenty-two miscarriages were reported from 19 families. At least one miscarriage occurred in 38% of the families, three families experienced two miscarriages and 16 families had one miscarriage each. The mean miscarriage rate was 15.8%. The heterozygous mothers had a total of 90 siblings (41 m, 49 f), while 74 siblings (33 m, 41 f) were reported from the heterozygous fathers. The miscarriage rate was 10.1% in the families of the mothers` siblings, and 11.4% in the families of the fathers` siblings. The genotype was known in all parents that have an offspring with classic CAH, but not defined in 82% of the maternal siblings, and in 86% of the paternal siblings. No child with classic CAH has been diagnosed in any of the sibling's families to date. CONCLUSION: Our data show that the miscarriage rate in German families with a child with classic CAH is not elevated.
EVALuna2:35501

Short-term adverse effects of testosterone used for priming in prepubertal boys before growth hormone stimulation test - Albrecht, Andrea; Penger, Theresa; Marx, Martin; Hirsch, Karin; Dörr, Helmuth-Günther (Journal of Pediatric Endocrinology & Metabolism, 2018)
BACKGROUND: Despite the fact that priming with sex steroids in prepubertal children before growth hormone (GH) provocative tests is recommended, there is an ongoing controversial discussion about the appropriate age of the children, the drug used for priming, the dose and the period between priming and the GH test. Interestingly, there is no discussion on the safety of this procedure. To date, only little data have been available on the possible side effects of priming with testosterone. METHODS: We analyzed the outcome in 188 short-statured prepubertal boys who had been primed with testosterone enanthate (n=136: 50 mg; n=51: 125 mg, and accidentally one boy with 250 mg) 7 days prior to the GH test. Serum testosterone levels were measured on the day of the GH test in 99 boys. RESULTS: Overall, only five boys developed adverse side effects. Two boys (dose 125 mg) showed severe low-flow priapism and had to undergo decompression of the corpora cavernosa. One boy suffered from self-limiting priapism and testicular pain (dose 50 mg). Two patients reported testicular pain (each dose 50 mg). The single patient with 250 mg testosterone did not show any adverse effects. The total side effect rate was 2.7%. The serum testosterone levels of the boys with side effects were not different from the testosterone levels of the boys without any side effects. CONCLUSIONS: Parents and patients should be informed about the possible side effects of priming with testosterone such as priapism and testicular pain. However, the overall side effect rate is low. We found no correlation between the outcome and the testosterone dose used and/or the level of serum testosterone.
EVALuna2:35502